“Collecting spring water reminds us how to be human”: in search of an ethic of care for the springs of southern Cape Town - Tyrrell, Jessica (School of Languages and Literatures, 2021)
Between 2015 and 2018 Cape Town was affected by a drought more severe than any on record. When it became clear that Cape Town might actually run out of water, thousands of its citizens flocked to the historical springs that flow from Table Mountain's groundwater, which for many of whom it was their first time collecting spring water. However, at the height of the water crisis, the municipality cemented over one of these vital springs after numerous complaints of disturbance by residents. Piped to a newly constructed water collection site enclosed by fences a kilometer away, the water was made accessible to the public through 16 industrial taps. While this action from the municipality may have been the only viable solution, it was experienced as a huge loss to the people of Cape Town. This study investigates why the design of the current spring water collection point became the source of such criticism. It compares the re-designed site with two of Cape Town's southern springs that still flow freely, investigating the meaning and influence of unrestricted flowing spring water through public engagement on site, asking what draws people to collect spring water. Key themes that emerged include health and wellbeing; and connection with other humans, with history, with nature and with a greater spirit. Springs are powerful agents for an ethic of care, the study finds, and water a powerful medium of connection. Yet, the city's water policies are shaped by the kind of thinking that sees water only as a commodity, reflected in an urban design that further alienates people from water and nature. In this era of the Anthropocene, itself a condition of this alienation of people from the earth, the paper concludes and proposes biophilic design principles that foster the sensibilities of connection and interdependence as a vital part of urban design for a shared future where people come to know what it means to be human as participants within a living world.